problem based learning and material changes - emmi juwita siregar emmi juwita (Jurnal Education and Development, 2017)
This study aims to know whether there is a significant influence of using problem based learning model on students’ achievement on the topic of material changes at seventh grade students of SMP Negeri 2 Padangsidimpuan. This research was conducted by applying experimental method with sample 30 students. Descriptive and inferential statistics were used to analyzed the data. Based on the analysis, it could be found that (1) the average of using problem based learning model is 443(good category), (2) robservedis greater than than 0.05 (0.04<0.05), it means, there is a significant correlation of using problem based learning model on students’ achievement on the topic of material changes, and (3) tobservedis greater than 0.05 (0.008<0.05), it means there is a significant influence of using problem based learning model on students’ achievement on the topic of material changes at seventh grade students of SMP Negeri 2 Padangsidimpuan.